PENGARUH KERJASAMA ORANGTUA DAN GURU TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK KELAS B PAUD IT BUNAYYA - Aminoh Kiya; Alucyana Alucyana (UIR PRESS, 2021)
This study aims to determine the effect of parent-teacher cooperation on the socio-emotional development of early childhood in class B PAUD IT Bunayya. By using quantitative research methods, the subjects of this research are the parents of class B PAUD IT Bunayya students, totaling 64 students. This study wanted to know whether or not there is an influence between two variables, namely the cooperation of parents and teachers and the social-emotional development of early childhood. The data analysis technique is the SPSS test. Based on the results of the study of hypotheses, the simple linear value of parent and teacher cooperation on children's social-emotional development is 16,793 with a sig. (2-tailed) value of 0.000. Compared to the significance level of 0.05(5%), this sig. (2-tailed) value is greater than 0.05(5%). This means that there is an influence of the parent-teacher cooperation variable on the emotional social development of early childhood in class B PAUD IT Bunayya. The researcher saw the magnitude of the coefficient of determination (R square) which was 0,213 which showed the magnitude of the influence of parent and teacher cooperation on children's social-emotional development.